BENTUK, KEUTAMAAN, DAN LANGKAH-LANGKAH MENEMUKAN TAFSIR RASULULLAH SAW - Irsyad Al Fikri Ys (LP2M IAIM Sinjai, 2021)
Tafsir in the form of the Qur'an and the Sunnah of the Prophet is the interpretation of the highest value because some verses of the Qur'an are marginal (global) so in other parts, there are relatively detailed descriptions. If it is not contained in the Qur'an, then the Sunnah of the Prophet is the explanatory and explanatory of the Qur'an. From this, it can be seen that the Prophet Muhammad was named the first mufassir to interpret the Qur'an. To arrive at knowledge about the steps to find the interpretation of the Prophet Muhammad, it is necessary to have a special study on this matter. In summary, this paper will describe how the motives and forms of interpretation of the Prophet and the approach used by the Prophet in interpreting the Qur'an, both with the Qur'an itself and with al-Hadith. From here it will be known how the characteristics of the Prophet's interpretation itself and the Privileges of the Prophet's Tafsir which became the initial reference for the birth of new interpretations in the next generation.